Computer-Aided Entry Point Localization and Insertion Path Planning of Intramedullary Nail Using CT Imaging - Xiaolong Liu; Jin Li; Kuan Luan (IEEE Access, 2024)
Intramedullary nailing is frequently utilized in the treatment of femoral shaft fractures. However, an incorrect entry point will result in poor reduction of the shattered bones. Furthermore, intramedullary nails frequently encounter obstacles during insertion. The goal of this study contains two parts: 1) determining the ideal entry point and drill-hole shape for a given patient with its well-matched intramedullary nail (IMN), and 2) planning an appropriate insertion path for the IMN. Computed tomography scans from patients’ femurs and their well-matched IMNs are obtained to generate three-dimensional models and centerlines. A centerline self-growing strategy that combines four evaluating factors is employed to determine optimal centerline segments and align the IMN with the medullary cavity. For the first objective, the position of entry point under the optimal registration is computed. The drill-hole shape comprises all the intersections between the IMN and the femur near the entry point at 5 different depth positions. For the second objective, a visualized planning path including a series of the positions and postures is established through optimal registration. A local coordinate system is defined at the endpoint of the IMN. The transformation parameters between adjacent positions are computed for intra-operative guidance. The method was verified using the four experiments: entry point evaluation, path feasibility, path effectiveness, and IMN insertion guidance. During the whole insertion process, the maximum distance between the IMN centerline and the center point of the narrowest position of the medullary cavity is 0.673 mm, which meets clinical requirements. The IMN insertion guidance experiment demonstrates that the determined path is appropriate. In the path effectiveness experiment, the IMN can be successfully inserted into the medullary cavity, the upper and lower broken bones fit tightly without displacement, and the average time taken to plan an insertion path using this method is 9.37 min. The experimental results show that when the IMN is inserted according to the determined entry point and drill-hole, the shattered bone cracks fit closely. Additionally, the IMN can be successfully inserted without obstacles following the planned path which can minimize the damage to intramedullary tissues.